CYBERPORN ANALYSIS IN THE PERSPECTIVE OF THE IUS CONSTITUTUM IN INDONESIA - Muhammad Zulhidayat (Universitas Muhammadiyah Tangerang, 2020)
Technology and the internet continue to experience extraordinary developments. The progress of the internet has brought a lot of positive progress towards a country. However, the internet can also negatively affect a nation. Many new crimes arise with the development of technology and the internet, one of which is cyberporn crime. In simple terms, cyberporn is also called the sin of pornography by using the internet as a crime tool. Based on the facts that we have found to date, cyberporn crimes continue to increase. This is a result of technological and internet developments that are not used well. The research in this paper uses a normative juridical approach. The research in this paper uses a prescriptive legal approach. The formulation of the problem is how is the regulation of cyberporn crimes a positive law in Indonesia? This research concludes that a constitutional renewal is needed with this cyberporn crime. Because the existing legislation cannot punish the perpetrators of cyberporn crimes. Then, the suggestions in this research include the House of Representatives (DPR) to formulate a law that explicitly regulates the problem of cyberporn crime.Keywords: crime, cyberporn, ius constititum